Divided solids mechanics - Duroudier, Jean-Paul (Industrial equipment for chemical engineering set., 2016)
Divided Solids Mechanics, part of the Industrial Equipment for Chemical Engineering set, defines how to perform the selection and calculation of equipment needed in the basic operations of process engineering, offering reliable and simple methods, with this volume providing a comprehensive focus divided solids mechanics. Throughout these concise and easy-to-use books, the author uses his vast practical experience and precision knowledge of global research to present an in-depth study of a variety of aspects within the field of chemical engineering.